State autonomy and industrialization in Turkey between 1960 and 2000 - Tanaydın, Sergen (My University, 2019)
The rapid development of the East Asian countries until 1980 and the fact that these countries also maintained this success in 1980s without facing a crisis received widespread attention in development economics literature. Organizations like IMF and WB and economists praising liberal policies have attributed this success to liberal policies and to the export-oriented growth while development economists emphasized the role of governments in development processes. Governments in these countries have established policies in a way to serve industrialization through state autonomy and have not allowed any class to undermine these policies and process for their own benefit. Although the Latin America countries began their industrialization thrust before East Asia countries, they could not maintain their industrialization without facing financing bottleneck or crisis and they could not deepen their industrialization like East Asian countries. Turkey proceed to the planned development period in 1960. Until 1980, import substitution industrialization policy and wide interventionist policies were followed in the same way as Latin America and Asian countries. In 1980, this strategy was abandoned and export oriented development model and liberal policies were adopted. While the positive developments took place in industrialization indicators during the 1960-1980 period, it was observed that the progress towards industrialization reversed in the 1980-2000 period. In this study, Turkish industrialization of the 1960-2000 period have examined in state autonomy perpective comparatively with the industrialization moves of East and Southeasth Asia and Latin America countries. It have been concluded that the lack of state autonomy prevented further industrialization in the 1960-1980 period and constituted the cornerstone of the negative developments in industrialization in the 1980-2000 period. The findings of the study reveal the importance of governments that have autonomy to implement policies, which have been diagnosed as policies providing development.

Doğu Asya ülkelerinin 1980’e kadar gerçekleştirdiği hızlı kalkınma öyküsü ve bu ülkelerin 1980’lerde de bu istikrarı bir krize yakalanmadan devam ettirmesi kalkınma iktisadı literatüründe kendisine çok geniş yer buldu. IMF ve WB gibi uluslar arası kuruluşlar ve liberal politikaları öven iktisatçılar bu başarıyı liberal politikalara ve ihracata yönelik sanayileşme politikasına atfederken, kalkınmacı iktisatçılar hükumetlerin sanayileşmede üstlendiği role dikkat çektiler. Bu ülkelerdeki hükumetler sahip olduğu devlet otonomisi sayesinde politikaları sanayileşmeyi sağlayacak şekilde oluşturmuşlar ve herhangi bir sınıfın kendi çıkarları uğruna bu politikaları ve süreci baltalamasına izin vermemişlerdir. Latin Amerika ülkeleri ise ithal ikameci sanayileşme politikasına Doğu Asya ülkelerinden daha önce başlamasına rağmen sanayileşmelerini hem darboğaz veya krizle karşılaşmadan sürdürememişler hem de Doğu Asya ülkelerinin başarısına ulaşamamışlardır. Türkiye ise 1960’ta planlı kalkınma döneme geçiş yapmıştır. 1980 yılına kadar ithal ikameci sanayileşme politikası ve tıpkı Latin Amerika ve Asya ülkelerinde olduğu gibi geniş müdahaleci politikalar izlenmiş, 1980 yılı ile birlikte bu stratejiden vazgeçilerek ihracata yönelik kalkınma modeli ve liberal politikalar benimsenmiştir. 1960-1980 döneminde sanayileşme göstergelerinde olumlu değişimler yaşanırken, 1980-2000 döneminde sanayileşmeye dair ilerlemenin terse döndüğü gözlemlenmiştir. Bu çalışmada hem 1960-2000 dönemi Türk sanayileşmesi devlet otonomisi bağlamında irdelenmiş hem de Doğu ve Güneydoğu Asya ve Latin Amerika ülkelerinin sanayileşme hamleleri ile karşılaştırılmıştır. Devlet otonomisi eksikliğinin 1960-1980 döneminde daha ileri sanayileşmeyi engellediği, 1980-2000 döneminde ise sanayileşmede yaşanan gerilemenin kökenini oluşturduğu sonucuna varılmıştır. Çalışmanın bulguları, kalkınmayı sağlayacak politikalar teşhis edildiğinde bu politikaları uygulayabilme kapasitesine sahip hükumetlerin önemini ortaya koymaktadır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Industrialization; State autonomy; Interest groups; Planned period development; Sanayileşme; Devlet otonomisi; Çıkar grupları; Planlı dönem kalkınması